(untitled) (Innovative professional education, 2024)
Taking into account the urgency of the post-war reconstruction of Ukraine, the training of qualified workers, including the so-called "creative" professions, is becoming important. One of these is the profession of "Wood and birch carver", which can be mastered at the Byla Tserkva Vocational Lyceum. The woodcarver remains one of the national types of applied art to this day. After graduation, graduates can work at enterprises producing art products. If you wish, you can start your own business for the production of your own products.